Playing-related musculoskeletal disorder among classical piano students of tertiary institutions in Kuala Lumpur and Selangor, Malaysia - Lim, Chia Ying (2014)
Pianists often suffer from playing-related musculoskeletal disorders (PRMD) due to the long hours of static playing posture, playing technique, lifestyle, working conditions and other factors. It has been reported that musicians have a risk of injury with incidence ranging from approximately 30% to 90% in the shoulder-arm-hand region and within the spine. PRMD have been extensively studied overseas but injuries caused by piano playing have not been given adequate attention in Malaysia. Thus, this thesis focuses on PRMD among music students who are majoring in classical piano. The purpose of the study is to identify the extent of PRMD among classical piano students in tertiary institutions in Kuala Lumpur and Selangor. This also includes the level of knowledge about PRMD and finding possible risk factors for PRMD. A survey was conducted and 192 sets of questionnaires were collected. A total of 35.4% (68) students were found to suffer from PRMD. The shoulder was the part most commonly affected, followed by PRMD in arm, finger and wrist. Pain, fatigue and stiffness were most cited by those who suffered from PRMD. 58.3% (112) respondents had heard of at least one general term that describes pianists’ injuries. However, most of the students (71.4%) were not familiar with the specific examples of PRMD given at all. Results showed significant relationship between practice hours (p=0.031), the habit of taking a break in the middle of practice (p=0.045), physical cool down exercises (p=0.037) and special dietary intake (p=0.007) and the occurrence of PRMD when tested via Chi-square analysis. Classical piano students should be educated about the prevention of PRMD since PRMD are reported at various levels. It is hoped that the study will increase awareness of PRMD among musicians and encourage prevention of injury in musicians of different levels in the future because prevention is better than cure.